1989
DOI: 10.1136/ard.48.4.312
|View full text |Cite
|
Sign up to set email alerts
|

A study of headaches and migraine in Sjogren's syndrome and other rheumatic disorders.

Abstract: SUMMARY Migraine occurs with increased frequency in patients with systemic lupus erythematosus and in subjects suffering from Raynaud's phenomenon without any underlying connective tissue disorders. A possible link between migraine and Raynaud's phenomenon has been suggested. Two rheumatic conditions where Raynaud's phenomenon occurs very commonly are scleroderma and primary Sjogren's syndrome. It is possible that migraine is also common in these disorders but has been unrecognised. Therefore, the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 8 publications
(2 reference statements)
1
28
1
Order By: Relevance
“…As Bowdler et al showed, 42 it most likely reflects drug availability and preferences. Studies addressing headache prevalence in patients with rheumatologic disorders are scant, but do suggest migraine prevalence similar to the general population 48 . The 1‐year prevalence of migraine in our total sample group was higher and for TTH lower than the respective population prevalence 49,50 .…”
Section: Commentscontrasting
confidence: 52%
“…As Bowdler et al showed, 42 it most likely reflects drug availability and preferences. Studies addressing headache prevalence in patients with rheumatologic disorders are scant, but do suggest migraine prevalence similar to the general population 48 . The 1‐year prevalence of migraine in our total sample group was higher and for TTH lower than the respective population prevalence 49,50 .…”
Section: Commentscontrasting
confidence: 52%
“…Increased TGF‐β plasma levels were found in 29 of 31 HHT patients (33), but did not differ between HHT‐1 and ‐2. Interestingly, systemic sclerosis, another disease with increased serum TGF‐β levels (34), is also associated with migraine (35).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of migraine in BD is open to discussion. It has been suggested that small vessels disease, characterizing several multisystemic vasculitis, such as systemic lupus erythematosus, Sjogren's syndrome, scleroderma but also BD, may cause cerebrovascular dysregulation, leading to migraine (11). However, we did not find any relationship between disease activity and the frequency, duration, and severity of migraineous attacks.…”
Section: Discussionmentioning
confidence: 99%